Recursos didácticos tecnológicos en el tercer año de bachillerato, especialidad informática de la asignatura de desarrollo y evaluación de aplicaciones informáticas del colegio de bachillerato “Dr. Camilo Gallegos Dominguez” del cantón Arenillas, provincia de El Oro, periodo lectivo 2015-2016.- lineamientos alternativos - Guamán Gutiérrez, Samantha Anabell (2016)
This research arises from the dynamic analysis of the technological teaching resources today in educational process, for this reason and for a study of the current situation, the following item set: “RECURSOS DIDÁCTICOS TECNOLÓGICOS EN EL TERCER AÑO DE BACHILLERATO, ESPECIALIDAD INFORMÁTICA DE LA ASIGNATURA DE DESARROLLO Y EVALUACIÓN DE APLICACIONES INFORMÁTICAS DEL COLEGIO DE BACHILLERATO “DR. CAMILO GALLEGOS DOMÍNGUEZ” DEL CANTÓN ARENILLAS, PROVINCIA DE EL ORO, PERIODO LECTIVO 2015-2016.- LINEAMIENTOS ALTERNATIVOS.” The central problem of the research was: are applying technological teaching aids in the third year of secondary education specialized computer for the course development and evaluation of applications: High school "Dr. Camilo Gallegos Dominguez"? Under this provision was proposed as general objective: To investigate the impact of the application of technological teaching resources used in the course of Development and Evaluation of Computer Applications College High School "Dr. Camilo Gallegos Dominguez" The methodology is based on the deductive method, just as in the inductive method and synthetic method that permitted inferences and generalizations which led this research. All this allowed the analysis of the theoretical contents to process information obtained through techniques such as observation guide, interviews and surveys, applied to 23 students and one teacher. According to the results it is concluded that: 43% of students surveyed said that among the new technological resources that would like to learn in class are multimedia applications, 17% through virtual learning environments, technological resources that can be applied to classroom activities to make them more fun and interactive, in order that students gain significant learning also determined that the use and application of technological teaching resources by teachers in the process of teaching - learning, improving significantly student learning